Writing Organizational Tales: The Cultures of Work Organizations - Trice, Harrison M.; Beyer, Janice M. (Organization Science, 1995)
The meta-theme of this book is integration of diverse perspectives on culture and on organizations. In this book, we bring together various cultural perspectives, main-stream theories of organizations, and empirical work from various social science disciplines on cultural phenomena in organizations. The inclusiveness of our approach allows us to tell many stories about organizational cultures.